The Effect of Corporate Governance on Firm Performance - Harjum Muharam; Nirmala Luthfiya Atyanta (Journal of Economics and Business, 2021)
This study aims to analyze the effect of corporate governance mechanisms on firm performance. The sample used in this study were companies listed on the Indonesia Stock Exchange (IDX) during the period of 2016 to 2019. The number of samples used in this study was 100 samples. The sampling technique used is purposive sampling method. The research data was obtained from the company’s annual report. This study uses multiple regression analysis method which operated through data processing program IBM SPSS Statistics 25. The results of this study showed that the proportion of independent commissioner, audit committee, and institutional ownership had a positive and significant effect on Adjusted Tobin’s Q. Meanwhile, size of board of directors and managerial ownership found to had no effect on Adjusted Tobin’s Q. Firm size and firm age as control variables found to had a positive effect on Adjusted Tobin’s Q, while leverage found to had no effect on Adjusted Tobin’s Q.